IMPROVING THE STUDENTS’ READING COMPREHENSION OF EXPLANATION TEXT BY USING MAKE A MATCH TECHNIQUE AT THE ELEVENTH GRADE OF SMA SWASTA SANTU XAVERIUS GUNUNGSITOLI IN 2022/2023 - Daeli, Rosmine; Harefa, Afore Tahir; Zebua, Elwin Piarawan (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The objective of this research is to determine whether there is an improvement in students' reading comprehension after being taught using the 'Make a Match' technique. The researcher employed a classroom action research design conducted over two cycles. The research focused on the students of XI IPS 2. The instruments utilized for this study were a reading test and an observation sheet. The results of each cycle revealed that in Cycle I, the technique was not successful. Therefore, the research continued to the next cycle after revising the plan based on the weaknesses identified in Cycle I. The findings of Cycle II indicated that 19 students (67.85%) reached the 'good' level, while 7 students (25%) achieved the 'very good' level. These results demonstrate that the implementation of the 'Make a Match' Technique in this study successfully enhanced students’ reading comprehension.